2016
DOI: 10.1007/s00705-016-3010-9
|View full text |Cite
|
Sign up to set email alerts
|

Group A rotavirus in Brazilian bats: description of novel T15 and H15 genotypes

Abstract: This study aimed to survey for group A rotaviruses (RVA) in bats from Brazil and to perform phylogenetic inferences for VP4, VP7, NSP3, NSP4 and NSP5 genes. RVA was found in 9.18 % (28/305) of tested samples. The partial genotype constellation of a Molossus molossus RVA strain was G3-P[3]-Ix-Rx-Cx-Mx-Ax-Nx-T3-E3-H6, and that of a Glossophaga soricina RVA strain was G20-P[x]-Ix-Rx-Cx-Mx-Ax-Nx-T15-Ex-H15. These findings demonstrate an important role of bats in RVA epidemiology and provide evidence of participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
19
2
2
Order By: Relevance
“…1). BLAST searches indicated that the VP7 gene segment of the study strain was also closely related to the Ecuadorian human RVA strain Ecu534 and bat RVA strain 3081/BRA detected in Brazil in 2013 (Asano et al, 2016) and showed nucleotide (amino acid) identities of 81.8% (96.4%) and 81.3% (95.3%), respectively (Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…1). BLAST searches indicated that the VP7 gene segment of the study strain was also closely related to the Ecuadorian human RVA strain Ecu534 and bat RVA strain 3081/BRA detected in Brazil in 2013 (Asano et al, 2016) and showed nucleotide (amino acid) identities of 81.8% (96.4%) and 81.3% (95.3%), respectively (Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
“…Several improvements in viral detection and characterization methodologies such as high-throughput next generation sequencing have led to a successful discovery and characterization of several novel viruses in bats, including enteric pathogens such as RVA (Luis et al, 2013; Waruhiu et al, 2017). However, since the first detection and characterization of a human-bat reassortant RVA from a Straw-colored Fruit bat in 2010 (Esona et al, 2010), a few of other bat RVA strains, detected and characterized from different bat species and different geographic locations have been reported (Asano et al, 2016; He et al, 2013; Sasaki et al, 2016; Waruhiu et al, 2017; Xia et al, 2013; Yinda et al, 2016). Among the reported bat RVA strains, only bat RVA strain 3081/BRA from Brazil was closely related in the VP7, NSP3 and NSP5 gene segments with the study strain from Suriname.…”
Section: Resultsmentioning
confidence: 99%
“…Recent years have witnessed considerable sequence data accumulation in public data bases pointing out the enormous genetic diversity within the Rotavirus genus. Viral metagenomics largely contributed to our understanding of this genetic diversity (Asano et al, 2016;He et al, 2013;Kluge et al, 2016;Li et al, 2011;Marton et al, 2015;Mihalov-Kovács et al, 2015;Theuns et al, 2016;Xia et al, 2014). Until the early 2000s RVA to RVG were considered as the only extant RV species (Estes and Greenberg, 2013;Matthijnssens et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, bats seem to serve as reservoirs of multiple RVA genotypes commonly found in heterologous host species. Consequently, batborne RVAs might pose some veterinary and public health risk (Asano et al, 2016;He et al, 2013;Xia et al, 2014). More recent data indicate that in addition to RVA, RVH may also infect bats (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bats are hosts of rotaviruses, and some strains of rotavirus are genetically related to other mammalian rotaviruses, although other strains are bat-specific 7,181 . The significance of bats as a reservoir for rotavirus transmission to other mammalian species (including humans) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%